Uso de agrotóxicos, contaminação de mananciais e análise da legislação pertinente: um estudo na região de Manhuaçu-MG - Alexandra Fatima Saraiva Soares (2011)
The introduction of toxic substances in aquatic ecosystems is one of the most complex causes of degradation of water quality used by consumers, especially regarding pesticides, most of them persistent and resistant to conventional drinking water treatment. Thus, the study of thistreatment process to remove pesticides is very important in the state of Minas Gerais, that contributed with approximately 48% of coffee produced in Brazil, in 2009. This culture requires several pesticides to control diseases and plagues. The area of this study is the regionof Manhuaçu-MG, situated in Rio Doce catchment, responsible by expressive coffee production and where the cancer, after ill defined causes, formed the second greater cause of deaths in the region. The main goal of this research is to assess the impact of the pesticidesused in coffee culture to the quality in superficial sources for public use in Manhuaçu. For so, it was chosen, using geoprocessing techniques, the most vulnerable source to contamination. After this selection, points of collected water samples were determinate to investigate the presence of pesticides in rain and dry seasons. Active ingredients that present more potential of contamination in superficial water were selected. This research was carried out considering the amount of pesticides used in the region (2007/2010), physiochemical properties of activeingredients, potential to cause cancer and risk estimative of water contamination by pesticides, applying Goss algorithms. From these results, the most polluting pesticides were identified and selected three active ingredients to be studied in laboratories (essays of Jar Test), to know the efficacy of removal by conventional drinking-water-treatment processes. The study also contemplated a model to know environmental destination of pesticides used in the region by fugacity approach (level I). The pesticides, in the study area, contaminated superficial waters mainly by transport related to soil in rain periods. The findings observed in the subcatchment selected already presented traces of use of pesticides in agriculture. From 40 waters samples analyzed, 67% were contaminated with pesticides in raining period and only 21% in dry period. The study also found that conventional drinking-water-treatment methods are notadequate to perform pesticides/metabolites removal (ETU, endosulfan and 1,2.4-triazole). In the subcatchment of the selected source, where were found in superficial waters, 24 pesticides of chemical groups organochlorine, organophosphate, pyrethroid, triazole and carbamates by GC/MS-MS and LC/MS-MS the main irregular occupations, by coffee crops in areas of permanent preservation, occurred in steep areas (inclination > 45º) and destined to riparian forests. At last, a critical valuation of the pertinent legislation (potability and environmental)was carried out and compared national and international regulations. It was evident that some substances of ostensive use and with potential of contamination superficial water and to cause cancer are not contemplated in Brazilian legislation.